2017
DOI: 10.1039/c6ra26956g
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxic trichothecene-type sesquiterpenes from the sponge-derived fungusStachybotrys chartarumwith tyrosine kinase inhibition

Abstract: Bioassay-guided fractionation of a sponge associated fungus Stachybotrys chartarum resulted in the isolation of 15 trichothecene-based sesquiterpenes with inhibitory effects against tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…A recent publication outlined the isolation and characterization of several new trichothecene metabolites—among them were satratoxins G and H . The authors reported their sample of satratoxin G to furnish crystals suitable for x‐ray crystallographic analysis, to which they were able to resolve the absolute configuration of the compound.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…A recent publication outlined the isolation and characterization of several new trichothecene metabolites—among them were satratoxins G and H . The authors reported their sample of satratoxin G to furnish crystals suitable for x‐ray crystallographic analysis, to which they were able to resolve the absolute configuration of the compound.…”
Section: Introductionmentioning
confidence: 73%
“…Initially identified by Eppley and Bailey, satratoxins G and H were characterized in full, but the contemporary spectral details are not readily available, even though numerical values have been updated . These compounds have been implicated as the causative agents in animal and human toxicosis, in particular neurotoxicity and inflammation as a result of inhalation leading to respiratory disorders .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 , 10 , 28 ]. Macrocyclic trichothecenes are produced by the genera Myrothecium [ 29 , 30 , 31 ], Podostroma [ 32 ], Stachybotrys [ 33 ], Calcarisporium [ 34 ], Cercophora [ 35 ], Cylindrocarpon [ 36 ], Dendrodochium [ 37 ], Phomopsis [ 38 ], and Verticinimonosporium [ 39 ]. It is worth noting that Baccharis , belonging to the Asteraceae family, is the only plant genus that can produce trichothecenes [ 40 ].…”
Section: Macrocyclic Trichothecenes and The Producing Strainsmentioning
confidence: 99%